Coletivos de pensamento acerca da investigação-ação no ensino de ciências: Contribuições na formação de professores para os anos iniciais - Pacheco de Lima, Kaliandra; Emmel, Rúbia (Góndola, enseñanza y aprendizaje de las ciencias, 2025)
This research had the general objective of: understanding the contributions of the authors of dissertations and theses research produced in Brazil on the formation of Science teachers for the Early Years and Action-Research (IA), in the constitution of styles and collectives of thought that characterize research on the subject, present in the analyzed database. The searches were limited to the following terms: Early Years; Teacher training; Science teaching; Research-Action. Six surveys were identified from 2013 to 2020, in which Content Analysis was used (Bardin, 1997). Thus, it was possible to identify 24 reference authors distributed in 46 registration units. The most frequent reference authors among the registration units were Carr and Kemmis (1988) with 31 registration units; Elliott (1990), with 15 recording units. We stress the importance of continuing to research and use AI for the development of research in science teacher training.